THE EXPLORATION OF BUTON ANCIENT MANUSCRIPTS AS A POTENTIAL FOR TOURISM DEVELOPMENT IN BAUBAU CITY - Rahmawati Rahmawati; Syaifuddin Syaifuddin; Heksa Biopsi Puji Hastuti; Derri Ris Riana (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
This study aims to (1) describe the potential of the Buton manuscript as tourism development in Baubau City; and (2) describe a manuscript-based tourism destination development model in Baubau City. The study was qualitative descriptive research. The research data used a literature study. Various journals, articles, and relevant books are sources of information related to the intricacies of the Buton manuscript. The results show that (1) Buton’s manuscript has the potential as an object for cultural tourism development. In addition to Almujazi Mulku Zahari who collected ± 320 manuscripts, these manuscripts have been cataloged by Ikram et al (2021), other Buton manuscripts were also collected by other people such as La Mbalangi (78 years), Moersidi (73 years) La Ode Aegu (80 years), La Ode Ansari Idris (68 years old), etc. The contents of the Buton manuscript include legislation, Islamic teachings, philosophy of life, history, medicine, love stories, covenant documents, and literature. (2) The Buton manuscript tourism development model can be carried out by managing the Buton manuscript as well as possible such as manuscript conservation so that it becomes more accessible to the public in the form of installing nameplates for manuscript heirs, making manuscript maps, strengthening the capacity of manuscript heirs, manuscript galleries, making a place for storing manuscripts, making social media for manuscript owners, photo galleries for manuscript owners, and tourism networks.